PEMBELAJARAN KEWIRAUSAHAAN DI PTAIN JAWA TIMUR: PERSPEKTIF STRATEGI PEMBELAJARAN - Idrus, Salim Al (Fakultas Ekonomi, UIN Maliki Malang, 2013)
Entrepreneurship education, as a local curriculum, is needed to enlarge and support the students’ skill. So it is needed modification of conventional education method to obtain information about education strategy of entrepreneurship at Islamic State PTAIN Jawa Timur of East Java. Findings obtained from the study are (1) the education process of entrepreneurship subject in Islamic State PTAIN Jawa Timur of East Java is given by a master who has profession as a head of official functionary on fisheries institution in PTAIN Jawa Timur . He organizes the subject in a written summary that will be read in front of the class, (2) the class is started by giving the students real phenomenon to strengthened their view and it will be finished by giving them writing exercise or individual/group task; the students searching many literatures to be resumed. Lecturer is used as a media and the method used are lecture, discussion, and literature, (3) Creating students’ interest into the real phenomenon in order to strengthened students’ view. Pre-test and post-test given in written exercise or individual/group task will generate good studying motivation to each of the students and it also will increase interaction between lecturer and students on the subject studied.